2008
DOI: 10.1016/j.febslet.2008.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E dependent microRNA regulation in rat liver

Abstract: Dietary vitamin E (VE) is known to regulate gene expression by altering mRNA concentrations. Recently, micro-RNA (miRNA) have been discovered as a means of posttranscriptional gene regulation. Since the effect of VE on miRNA regulation is unknown, we fed rats for 6 months diets deficient or sufficient in VE and determined hepatic concentrations of miRNA involved in processes previously associated with VE (lipid metabolism, miRNA-122a; cancer and inflammation, miRNA-125b). VE-deficiency resulted in reduced conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 37 publications
4
86
0
2
Order By: Relevance
“…Real-time quantitative PCR was performed as a one-step procedure (SensiMixTM One-step Kit; Quantace, Berlin, Germany) with SybrGreen detection, using the Rotorgene 6000 cycler (Corbett Life Science, Sydney, NSW, Australia) (11) . Quantification was done using a standard curve.…”
Section: Rna Isolation and Real-time Quantitative Rt-pcrmentioning
confidence: 99%
“…Real-time quantitative PCR was performed as a one-step procedure (SensiMixTM One-step Kit; Quantace, Berlin, Germany) with SybrGreen detection, using the Rotorgene 6000 cycler (Corbett Life Science, Sydney, NSW, Australia) (11) . Quantification was done using a standard curve.…”
Section: Rna Isolation and Real-time Quantitative Rt-pcrmentioning
confidence: 99%
“…This indicates a pathway for targeted therapy via VDR downregulation in human malignancies [58]. Vitamin E modulates lipid metabolism, inflammation, and other cancer-associated pathways by altering the expression of miR-122 and miR-125b [59].…”
Section: Mirna Associated Epigenetic Regulation Mediated By Dietmentioning
confidence: 98%
“…On the contrary, vitamin E deficiency in rats decreased tumor suppressor miRNAs in the liver. Vitamin E has also has been reported to modulate lipid metabolism, inflammation, and other cancer-associated pathways by reducing the expression of miR-122 and miR-125b [127] . Vitamin D has long been considered as an essential nutrient for human health and evidence from epidemiologic and experimental studies have indicated that higher intakes of vitamin D from food and/or supplements leads to higher blood levels of vitamin D, which are highly associated with reduced risks of certain cancers [128,129] .…”
Section: Role Of Nutritive Natural Agents In the Regulation Of Mirnasmentioning
confidence: 99%